Optimalisasi Pemberdayaan Masyarakat Melalui Program Apotek Hidup dengan Pemanfaatan Limbah Plastik dengan Prinsip 3R (Reduce, Reuse, Recycle) - Riris Andriati; Andriyani Rahmah Fahriati; Fenita Purnama Sari Indah; Firdha Senja Maelaningsih (Universitas Medan Area, 2023)
The objectives of this Community Service include increasing the knowledge and skills of the Pasireurih Village community in planting and processing Family Medicinal Plants as well as processing waste through 3R (Reduce, Reuse, Recycle). Apart from that, it improves the skills of the people of Pasireurih Village. The method used to achieve the objectives of Community Service is by means of lectures (counseling) and training. A series of activities include counseling on family medicinal plants, training on planting and processing Family Medicinal Plants, as well as counseling on waste management. The result of this Community Service activity is that all series of Community Service activities run smoothly and provide satisfactory results. The Community Service activities that have been carried out have benefits in several sectors. The main sectors that have the most influence are health and the environment. The success of implementing activities can be seen from several components, namely: there is an increase in public knowledge regarding Family Medicinal Plants and waste processing through 3R. Apart from that, Family Medicinal Plants in people's homes has increased significantly, and people have become skilled in processing medicinal plants into herbal drinks. The person responsible for Family Medicinal Plants has also created its management.